(untitled) (Research, Society and Development, 2021)
Many school practices show just a juxtaposition of disciplines, in which each teacher, in his/her class, addresses some specific concepts, making it difficult for students to spontaneously transfer knowledge from one discipline to another. These practices were overcome in an interdisciplinary work between the disciplines of physics and building systems of the third year of the technical course in buildings integrated to the high school of the "Instituto Federal de Educação, Ciência e Tecnologia Farroupilha, Campus Santa Rosa/RS". Through the elaboration, development, and evaluation of a Potentially Meaningful Teaching Units (PMTUS) about simple electrical circuits, teachers of both disciplines developed together the specific concepts of their disciplines in an integrated manner, considering that these are convergent. Based on the results, the following text aims to investigate the implications of interdisciplinary work between the disciplines of physics and building systems for the students’ meaningful learning about simple electrical circuits in some steps of the PMTUS, the students elaborated interdisciplinary conceptual maps and built a residential electrical project, with their houses as reference. The construction of these instruments was assisted by both teachers, and they were used as evaluative instruments by both disciplines. Both in the conceptual map and in the electrical project, students showed signs of meaningful learning, sharing the knowledge of the disciplines, which ratifies the achievement and the importance of an interdisciplinary work to promote meaningful learning.